ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI JOB PERFORMANCE PADA INDUSTRI ASURANSI DI BATAM - Adi Neka Fatyandri; Daniel Oktaf Theosandoro (Journal of Accounting and Management Innovation, 2019)
Growth in the insurance industry in Indonesia is very rapid and also tight and because of that insurance company will have to continuously improve the Job Performance of their employees so that they will be able compete in the industry. This study was conducted to analyze several factors that influence the Job Performance. These factors are Caring Climate, Organizational Commitment and Job Satisfaction.The samples are workers who work in the insurance industry in Batam, Indonesia. 115 questionnaires have been distributed to several insurance companies in Batam. There are 7 questionnaire weren’t fully answered and 8 questionnaires weren’t returned, so only 100 questionnaire will be used in conducting the study.The results of the research that was carried out showed that two factors affecting the Job Performance of workers employed in the insurance industry in Batam, those factors are Caring Climate and Organizational Commitment. While Job Satisfaction did not affect Job Performance. Keywords: Job Performance, Caring Climate, Organizational Commitment dan Job Satisfaction